Frequency of Medical Complications in Hospitalized Stroke Patients at Bahawal Victoria Hospital, Bahawalpur (Medical Forum Monthly, 2024)
Objective: To find out the frequency and nature of medical complications in hospitalized patients admitted to Bahawal Victoria Hospital, Bahawalpur with acute stroke.Study Design: Cross-sectional StudyPlace and Duration of Study: This study was conducted at the Department of Medicine, Bahawal Victoria Hospital & Quaid-e-Azam Medical College, Bahawalpur from July 2015 to September 2015.Materials and Methods: 98 patients who fulfill the inclusion criteria and gave informed consent were enlisted in the study. These patients were regularly observed for any post stroke medical complications after the clinical evaluation and CT scan plain brain until they were discharged from the hospital.Results: The mean age of the patients was 57.15 + 15.42. Most of the patients suffering from stroke were female (68.4 %) and belonged from rural population (73.5 %). Most of them were suffering from ischemic stroke (66.3 %). Specified medical complications included: Recurrent Stroke (29.6 %), Epileptic seizures (12. 2 %), Urinary tract infections (30. 6 %), respiratory tract infections (31. 6 %), bed sores (15.3 %), shoulder pain (10.2 %), depression (53.1 %), falls (13.3 %), Venous Thromboembolism (7.1 %). A total of 14 patients (14.28 %) died during the hospital stay due to severe disease.Conclusion: This study established the post stroke medical complications mainly the pressure sores, pain and infection. As a complication, depression was also identified among the stroke patients. The disability and mortality can be minimized by early identification and treatment of these likely avertable complications.